2019
DOI: 10.1007/s42452-019-1302-x
|View full text |Cite
|
Sign up to set email alerts
|

Novel green synthesis of silver nanoparticles using clammy cherry (Cordia obliqua Willd) fruit extract and investigation on its catalytic and antimicrobial properties

Abstract: In this study, highly monodispersed, exceptionally stable, spherical silver nanoparticles (AgNPs) were successfully synthesized by the microwave assisted rapid and cost-effective green method. Aqueous extract of clammy cherry (Cordia obliqua Willd) fruit was used as the green reductant, and capping agent for the synthesis of AgNPs and the effect of different synthesis parameters on the optical properties of the synthesized AgNPs was also studied. The characterization of synthesized AgNPs by Fourier transform i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…13 nm, thus displayed easy cell disruption of various human pathogens. 239 Besides, antimicrobial activity of various fruit extract such as Abelmoschus esculentus, 244 Phyllanthus emblica, 245 Aegle marmelos, 246 Nauclea latifolia, 247 Myristica fragrans, 248 Capsicum frutescens 249 and Areca catechu 250 mediated AgNPs was also tested and found that the synthesized AgNPs displayed great cell disruption of bacterial strains. The effect of solvent extract of Aegle marmelos on antimicrobial activity was tested by making fruit extract in various solvents such as petroleum, ether, methanol, acetone and chloroform and found that methanol extract of Aegle marmelos displayed highest cell disruption against B. cereus and lowest for E. coli.…”
Section: From Fruitmentioning
confidence: 99%
See 1 more Smart Citation
“…13 nm, thus displayed easy cell disruption of various human pathogens. 239 Besides, antimicrobial activity of various fruit extract such as Abelmoschus esculentus, 244 Phyllanthus emblica, 245 Aegle marmelos, 246 Nauclea latifolia, 247 Myristica fragrans, 248 Capsicum frutescens 249 and Areca catechu 250 mediated AgNPs was also tested and found that the synthesized AgNPs displayed great cell disruption of bacterial strains. The effect of solvent extract of Aegle marmelos on antimicrobial activity was tested by making fruit extract in various solvents such as petroleum, ether, methanol, acetone and chloroform and found that methanol extract of Aegle marmelos displayed highest cell disruption against B. cereus and lowest for E. coli.…”
Section: From Fruitmentioning
confidence: 99%
“…However, to inhibit the growth of bacteria S. aureus , a comparatively high concentration of AgNPs is required. 236 There are several reports where different fruit extract such as Terminalia bellirica , 238 clammy cherry, 239 Phyllanthus emblica , 240 Forsythia suspense , 241 Rosa canina 242 and Manilkara zapota (Sapota) 243 have been productively utilized for the green synthesis of AgNPs and evaluate their bactericidal activity against various bacterial pathogens. The results revealed that, AgNPs generated from each fruit extract displayed great antimicrobial activity against both Gram-negative and Gram-positive bacteria.…”
Section: Plant-mediated Biogenic Synthesis Of Agnps and Their Antimic...mentioning
confidence: 99%
“…In other investigations, Cordia obliqua Willd. fruits were used for the synthesis of silver nanoparticles (Bharathi et al 2018, Saidu et al 2019. In both cases, antibacterial activity was observed against Staphylococcus aureus and Escherichia coli compared to commonly used antibiotics employing nanoparticle concentrations between 30 to 100 µg/mL Additionally, antibacterial activity against Bacillus circulans and Pseudomonas aeruginosa have been shown (Saidu et al 2019).…”
Section: Nanoparticlesmentioning
confidence: 99%
“…Different ancestral medicinal properties have been attributed to the genus due to its antibacterial, antioxidant, anthelmintic, anti-inflammatory, and analgesic activity presented by its leaves, roots, flowers, and fruits (Hojjati & Beirami-Serizkani 2020, Rezende et al 2020. However, in recent years, the mucilage from the fruit of some species of the genus has been evaluated as a biopolymer for the development of pharmaceutical and food formulations, such as oral and dermal drug delivery systems (Duppala et al 2016, nanoparticles (Saidu et al 2019), edible coatings (Castro 2019, El-Mogy et al 2020, food additives (Hasani & Yazdanpanah 2020), among others. Both mucilage and gums are considered hydrocolloids, polysaccharides of high molecular weight, useful for the elaboration of various products in the pharmaceutical, food, cosmetic, and paint industries (Amiri et al 2021, Singh & Barreca 2020.…”
Section: Introductionmentioning
confidence: 99%
“…The phytochemical reduction method is comparatively slower than a conventional chemical reduction in earlier times. However, this limitation is resolved by using microwave-assisted synthetic techniques so that biological synthesis can be carried out rapidly with good yield [ 65 ]. Bioactive components or phytochemicals with various functional groups, such as hydroxyl, carbonyl, and amidogen groups, are ideal for adsorption on the metal surface to reduce Ag + to Ag 0 .…”
Section: Chinese Herbal Medicinementioning
confidence: 99%